A new species of the enigmatic genus Oressinoma Doubleday from the Andes of central Peru (Lepidoptera: Nymphalidae, Satyrinae) - Florczyk, Klaudia; Fåhraeus, Christer; Boyer, Pierre; Zubek, Anna; Pyrcz, Tomasz W. (Zootaxa, 2021)
A new, and only the third known species of the Neotropical montane genus Oressinoma Doubleday is described—O. sorina n. sp., from the Andes of central Peru. It is distinguishable immediately from the other two congeners by the shape of the hindwing underside submarginal orange band, and by the male genitalia. The systematics of Oressinoma are reviewed. A preliminary analysis is carried out based on COI barcode confirming the separate specific status of O. sorina n. sp. in relation to other two congeners. Both barcode and genital morphology data suggest that the widespread O. typhla Doubleday may be a complex of allopatric or, locally parapatric species. The genus Oressinoma is the only neotropical member of the predominantly Australian subtribe Coenonymphina, represented in the entire Holarctic by one genus only—Coenonympha Hübner, considered as the putative sister-genus of Oressinoma. Their origins and relationships are briefly discussed.